Peran Strategi Konseling Individual sebagai Solusi dalam Mengatasi Stres Akademik di Kalangan Mahasiswa - Muhammad Ubaydillah; Maulida Maghfiro; Moh Rifqi Naila Rizqillah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This article discusses academic stress as a serious problem that is often experienced by university students and has a negative impact on mental health and academic performance. To address this, individual counselling approaches are considered an effective solution. This study is a literature review that aims to evaluate the effectiveness of various individual counselling strategies in relieving academic stress. Using the literature review method, the study reviewed relevant literature from journals, books and reputable academic sources, with selection based on rigorous methodological criteria. Analyses were conducted systematically using a qualitative approach and a descriptive-analytical framework. The results showed that techniques such as relaxation training, time management, enhancing study skills, social support, self-regulation, and developing a positive and flexible mindset were effective. The role of professional counsellors was also identified as an important factor in successful counselling. This study makes both practical and theoretical contributions to the field of counselling, by providing strategic guidance for more targeted interventions. In addition, the findings open up opportunities for further research into approaches to handling academic stress.